A melanotic malignant melanoma presenting as a keloid: A case report. Issue 49 (December 2017) - Jia, Jinjing; Wang, Min; Song, Liumei; Feng, Yiguo
Abstract: Rationale: Amelanotic malignant melanoma (AMM) is a rare subtype of malignant melanoma (MM) that manifests atypically and is easily misdiagnosed or missed altogether. The keloid type of AMM has rarely been reported. Herein, we provide information to improve the clinical diagnosis of AMM types and raise awareness to ensure early diagnosis and timely treatment. Patient concerns: A 20-year old woman presented with a mass on her left shoulder of 1 year's duration that had been treated surgically. The lesion recurred 1 month before the present case, along with lymph node enlargement on the left supraclavicular fossa. Diagnoses: Histopathology and immunohistochemistry findings suggested AMM. Interventions: The original tumor recurred 1 month later after chemotherapy, and an extended resection and a second round of chemotherapy were performed. However, the patient exhibited suspected epileptic symptoms during chemotherapy and was required to return to the local hospital for treatment. Outcomes: No tumor recurrence occurred within a 6-month follow-up period. Lessons: Early AMM diagnosis has a very significant effect on prognosis. For some persistent and growing proliferative lesions, obliterative treatments should be avoided before a definitive histopathological diagnosis has been made.